KEGIATAN PRESERVASI KOLEKSI BAHAN PUSTAKA LANGKA DI PERPUSTAKAAN PUSAT TNI AD KOTA BANDUNG - Yunita, Hasna; Khadijah, Ute Lies; Kurniasih, Nuning (Pustakaloka, 2024)
This study aims to examine the implementation of preservation efforts undertaken for rare library material collections at the Central Library of the Indonesian Army History Service (Disjarahad). Furthermore, this research explores the challenges encountered in these preservation activities and identifies potential solutions. A qualitative research method with a case study approach was employed. Data were collected through interviews, observations, and literature reviews. Data were analyzed using the stages of data reduction, data presentation, and conclusion. The findings reveal that the Central Library of Disjarahad implements preventive preservation measures, including regulating temperature, light, and humidity, maintaining environmental conditions, using mothballs, conducting routine inspections, and installing air conditioning systems in the collection room. Factors contributing to the deterioration of rare materials include internal factors (paper quality) and external factors (including fire, water, light, temperature fluctuations, dust accumulation, collection storage, air pollution, human activity, biological agents, and rodents).